2016
DOI: 10.1214/16-aoas965
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of the El Niño-Southern Oscillation on extreme spatial temperature events over Australia

Abstract: When assessing the risk posed by high temperatures, it is necessary to consider not only the temperature at separate sites but also how many sites are expected to be hot at the same time. Hot events that cover a large area have the potential to put a great strain on health services and cause devastation to agriculture, leading to high death tolls and much economic damage. South-eastern Australia experienced a severe heatwave in early 2009; 374 people died in the state of Victoria and Melbourne recorded its hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…. , A T being short-tailed with finite lower and upper end points; this agrees with previous studies on extreme low and high temperatures (Thibaud et al 2016;Winter et al 2016). We also calculate the site-wise 80% and 90% quantiles of the estimated GPD distributions.…”
Section: Marginal Modellingsupporting
confidence: 88%
See 1 more Smart Citation
“…. , A T being short-tailed with finite lower and upper end points; this agrees with previous studies on extreme low and high temperatures (Thibaud et al 2016;Winter et al 2016). We also calculate the site-wise 80% and 90% quantiles of the estimated GPD distributions.…”
Section: Marginal Modellingsupporting
confidence: 88%
“…In some instances, interest lies in the largest values of a spatial process, such as determining the likely spatial extent of a flood event or a heatwave; example methods and applications can be found in Davison et al (2012), Winter et al (2016) and Tawn et al (2018). Approaches include max-stable processes (Smith 1990;Schlather 2002) and Pareto processes (Ferreira and De Haan 2014); these are applicable when locations experience concomitant extremes, which may not always be the case.…”
Section: Introductionmentioning
confidence: 99%
“…The conditional extremes model has the ability to be more flexible with asymptotic dependence classes; it can account for asymptotic independence and asymptotic dependence (Heffernan and Tawn, 2004;Keef et al, 2013). It can also be used to analyse more than two i.i.d variables more easily than copula-based methods 190 (Winter and Tawn, 2016); we restrict the theory provided here to the bivariate case. The conditional model has been used for different purposes: spatial or temporal dependence between extremes (Winter and Tawn, 2016;Winter et al, 2016), dependence between extreme hazards (Zheng et al, 2014) and even financial purposes (Hilal et al, 2011).…”
Section: Conditional Extreme Modelmentioning
confidence: 99%
“…It can also be used to analyse more than two i.i.d variables more easily than copula-based methods 190 (Winter and Tawn, 2016); we restrict the theory provided here to the bivariate case. The conditional model has been used for different purposes: spatial or temporal dependence between extremes (Winter and Tawn, 2016;Winter et al, 2016), dependence between extreme hazards (Zheng et al, 2014) and even financial purposes (Hilal et al, 2011). The conditional extremes model assesses the dependence structure between several variables conditioning on one being extreme and aims to model the conditional distribution.…”
Section: Conditional Extreme Modelmentioning
confidence: 99%
“…when c = 0. Models that capture asymptotic independence are less well established; see Ledford and Tawn (1996), Heffernan and Tawn (2004), Wadsworth and Tawn (2012) and Winter et al (2016) for some examples. We have shown that our model captures the property of asymptotic independence over space, while accounting for the complex non-stationarity of the extratropical cyclone system.…”
Section: Joint Risk From Windstormsmentioning
confidence: 99%